Changes in stability, phytonutrients, 3-chloropropanol esters and glycidyl esters of peanut oil-based diacylglycerols during heat treatment - Lv, Yongsi; Peng, Xianwu; Lee, Yee-Ying; Xie, Xiaodong; Tan, Chin Ping; Wang, Ying; Wang, Yong; Zhang, Zhen (Elsevier, 2024)
Diacylglycerol (DAG) is generally considered one of the precursors of 3-chloropropanol esters (3-MCPDE) and glycidyl esters (GEs). This study aimed to evaluate static heating and stir-frying properties of peanut oil (PO) and PO based 58% and 82% DAG oils (PDAG-58 and PDAG-82). Observations revealed that, phytonutrient levels notably diminished during static heating, with PDAG exhibiting reduced oxidative stability, but maintaining a stability profile similar to PO over a short period. During stir-frying, 3-MCPDE content initially increased and then decreased whereas the opposite was observed for GEs. Furthermore, as temperature, and NaCl concentration increased, there was a corresponding increase in the levels of 3-MCPDE and GEs, although remained within safe limits. When used in suitable concentrations, these findings underscore the potential of DAG, as a nutritionally rich and oxidatively stable alternative to conventional cooking oils, promoting the use of DAG edible oil in heat-cooked food systems. © 2024 Elsevier Ltd